2014
DOI: 10.1016/j.molonc.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of PIK3CA mutational status at the single cell level in circulating tumor cells from metastatic breast cancer patients

Abstract: Circulating Tumor Cells (CTCs) represent a "liquid biopsy of the tumor" which might allow real-time monitoring of cancer biology and therapies in individual patients. CTCs are extremely rare in the blood stream and their analysis is technically challenging. The CellSearch(®) system provides the enumeration of CTCs with prognostic significance in patients with metastatic breast cancer (mBC), but it does not allow their molecular characterization, which might be useful to identify therapeutically relevant target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
117
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(126 citation statements)
references
References 34 publications
3
117
0
1
Order By: Relevance
“…The relative rarity of CTCs in patients, especially at early disease stages, should also bring our attention to the representativeness of molecular characteristics of the few captured cells. Single-cell genomics [180][181][182][183] and transcriptomics [41,138,180,182,184] revealed significant interpatient molecular heterogeneity among CTCs.…”
Section: Resultsmentioning
confidence: 99%
“…The relative rarity of CTCs in patients, especially at early disease stages, should also bring our attention to the representativeness of molecular characteristics of the few captured cells. Single-cell genomics [180][181][182][183] and transcriptomics [41,138,180,182,184] revealed significant interpatient molecular heterogeneity among CTCs.…”
Section: Resultsmentioning
confidence: 99%
“…Schneck and colleagues analyzed CTCs using the SNaPshot method and found PIK3CA mutations in enriched CTC pools of 15.9% of patients with metastatic breast cancer ( 80 ). Other authors isolated single CTCs and reported strong heterogeneity in the PIK3CA mutational status among CTCs from individual patients (81)(82)(83). These single CTC analyses resulted in higher detection rates of PIK3CA mutations; however, more information about the occurrence of these mutations in the context of therapeutic interventions is urgently needed.…”
Section: Dna Levelmentioning
confidence: 99%
“…They reported that patients with a baseline CTC count ≥5/7.5 mL of blood had worse progression-free (HR 1.92; p < 0.0001) and overall survival (HR 2.78; p < 0.0001) than patients with a CTC count of <5/7.5 mL. More recently, Pestrin et al [92] reported the feasibility of using CTCs to test the heterogeneity of metastatic breast cancer by evaluating the mutational status of the PIK3CA exons 9 and 20 in both the single and pooled CTCs from 18 patients. Two patients were heterogeneous for the presence of PIK3CA mutations when sequencing analysis was performed on >1 single CTC and 1 patient showed a negative correlation between the PIK3CA status in the primary tumour (wild-type) and the matched CTCs (exon 20 mutation).…”
Section: State Of the Art In Breast Cancermentioning
confidence: 99%